Healthcare professionals face ethical challenges in managing care for neurodevelopmental disorders: a qualitative study in Lebanon - Mustafa Saleh; Hani Chanbour; Lara Saoudi; Ingrid Nader; Maryse Hayek (BMJ Open)
Objectives This study aimed to explore the ethical challenges faced by healthcare professionals (HCPs) in managing children and adolescents with neurodevelopmental disorders (NDDs) in Lebanon. The primary research question addressed how HCPs navigate ethical dilemmas related to patient autonomy, surrogate decision-making and communication in the context of severe cognitive impairments.Design Qualitative, cross-sectional study using semi-structured interviews. Thematic analysis was applied to identify key ethical challenges in clinical practice.Setting Participants recruited from a range of healthcare specialties, including paediatric neurology, general paediatrics and psychiatry, and registered with the Lebanese Order of Physicians.Participants Sixteen HCPs, including paediatric neurologists and psychiatrists, participated in the study. Participants were selected based on their experience in treating children and adolescents with NDDs. There were no exclusion criteria based on gender, ethnicity or years of experience.Interventions No formal interventions were applied. Participants were interviewed about their experiences and ethical challenges in managing patients with NDD.Primary and secondary outcome measures The primary outcome was the identification of ethical dilemmas faced by HCPs in clinical decision-making with patients with NDD. Secondary outcomes included insights into the strategies employed by HCPs to balance patient autonomy with surrogate decision-making and the communication challenges they face with patients’ families.Results Thematic analysis revealed several key ethical challenges, including (1) balancing patient autonomy with the need for surrogate decision-making, (2) tailoring healthcare to individual cognitive abilities and (3) navigating the complexities of communication with patients and their families. Participants emphasised the importance of assessing decision-making capacity on a case-by-case basis. The study also highlighted the need for specialised, patient-centred approaches that respect autonomy while considering the practical limitations imposed by severe cognitive impairments.Conclusions This study provides critical insights into the ethical considerations faced by HCPs in managing children and adolescents with NDDs. Further research is needed to develop training programs for HCPs that address these ethical challenges and promote patient-centred decision-making.